PERTUMBUHAN EKONOMI DALAM PERSPEKIF EKONOMI ISLAM - Zuhdi, Zaenu (IQTISHODUNA, 2008)
The economic growth is one of the hot topics in macroeconomics. Through economic growth analysis a nation knows its development, wealth and prosperity.Â  The growth is measured from income per head by indicating Gross National Product or Gross Domestic Product. This research aims to explore the economics growth paradigm from Islamic perspective since there is a main different point of view between Economics in Islam and capitalism associated with the way of living. Capitalism underlines on how to complete the needs with unlimited effort, while in Islam the economic must be based on tauhid, rububiyyah, khalifah dan tazkiyah principles. Thus, in Islam perspective, prosperity is not all about material goods but also considering the happiness in life after the death.